Stiffness of a recycled composite aggregate. Issue 110 (July 2018) - He, H.; Senetakis, K.; Coop, M.R.
Abstract: Recycled concrete aggregate (RCA) is a promising substitute for natural aggregates and the reuse of this demolished material would benefit the construction projects both economically and environmentally. A difficulty associated with the prediction of the behavior of RCA is because of its multi-composition which is linked to the grain size in consideration. In this study, a comprehensive laboratory testing program is conducted on different fractions of RCA for which the ratio of silicon over calcium increases for the coarser fractions due to the limitation of the cement mortar inclusion as the mean size increases. The study incorporates bender/extender element tests capturing small-strain constrained moduli, Young's moduli and Poisson's ratio of RCA fractions with different mean grain size and grain size distribution. For the uniform RCA fractions, the results showed that during isotropic compression, the specimens had a clear dependency of their dynamic properties on mean grain size. For the better graded specimens, it was shown that their behavior was dominated to some extend by the finer fraction they were composed rather than being affected equally by the different fractions they consisted of. The results also highlighted the sensitivity of the behavior of the samples to the over-consolidation stress history. For RCA, a multi-composition material, the grain size has a dominant role on the modulus – pressure relationship as well as the sensitivity of material behavior to stress history and these observations must be considered in the analysis of geo-structures where RCA is used as construction material. Highlights: Bender/extender element tests are conducted on a recycled-composite aggregate. The material has a multi-composition of aggregate and cement mortar. The increase of grain size results in decrease of the soft cement compound. The change of composition with size markedly affects the stiffness constants of the material. The observed trends are not commonly found in single-mineral type geo-materials.